ASSESSMENT OF PORT CONNECTIVITY INDICES FOR INDONESIA MARINE HIGHWAY: A SUPPORT FOR POLICY INTERVENTION IN SPEEDING UP ECONOMIC GROWTH - Pramita Dewi - Nim: 15113031 , Abilla
Indonesia marine highway is hypothesized to be materialized when there is connectivity between ports. Port connectivity shows the connection level of a port to others within a particular marine transportation network. This research aims to perform the port connectivity in a spatial-economic based. To perform port connectivity, Port Connectivity Indices (PCI) is utilized. PCI is used to measure intervention indicator and display map of Indonesia density marine route. The connectivity index is calculated by a linear growth model based on three parameters, i.e. 1) Growth Regional Domestic Product (GRDP) of an area where the port lies on, 2) export volume of a port, and 3) efficiency based on the total route distance that a port has towards another port inside the marine transportation network. The results of this research reveals that most of main ports in Indonesia have no connectivity value that is competitive with another port. Thus, they need the prioritization scheme of economic intervention to accelerate their economic growth and strengthen their industry in order to be part of Indonesia marine highway transportation system.